First measurement of the fraction of top-quark pair production through gluon-gluon fusion - Aaltonen, T; Adelman, J; Akimoto, T; Albrow, MG; Álvarez González, B; Amerio, S; Amidei, D; Anastassov, A; Annovi, A; Antos, J; Aoki, M; Apollinari, G; et al. (2008)
We present the first measurement of σ(gg→tt̄)/ σ(pp̄→tt̄). We use 0.96fb-1 of s=1.96TeV pp̄ collision data recorded with the CDF II detector at Fermilab. Using charged particles with low transverse momentum in tt̄ events, we find σ(gg→ tt̄)/σ(pp̄→tt̄)=0.07±0.14(stat)±0. 07(syst), corresponding to a 95% confidence level upper limit of 0.33, in agreement with the standard model next-to-leading-order prediction of 0.15±0.05. © 2008 The American Physical Society.